Consider the random variable X with probability density function $$f(x) = \begin{cases} 3x^2; & \text{ if, } 0 < x < 1 \\ 0; & \text{ otherwise } \end{cases}$$ Find the probability density function of $Y=X^2$.

This is the first question of this type I have encountered, I have started by noting that since $0<x<1$, we have that $0< x^2<1$. So $X^2$ is distributed over $(0,1)$. I'm not really sure how to progress or what method to take to actually find the pdf.

  • 4
    $\begingroup$ One way is to get the cdf and differentiate it. $\endgroup$
    – Pradhan
    Nov 26, 2014 at 22:15
  • $\begingroup$ I am able to get the cdf for X, but how do I find the cdf for Y? $\endgroup$
    – Modulus
    Nov 26, 2014 at 22:27

3 Answers 3


Note that $$F_Y(y)=P(Y\leq y)=P(X^2\leq y)=P(X\leq\sqrt{y})=F_X(\sqrt{y})=\int_0^\sqrt{y}3t^2\,dt=y^{3/2}$$ hence $$f_Y(y)=\frac{3}{2}\sqrt{y}$$

This holds for $0<y<1$.

  • 3
    $\begingroup$ The random variable can take negative values. $\endgroup$ Feb 26, 2017 at 21:29
  • 2
    $\begingroup$ @DiegoFonseca Can it? $\endgroup$
    – Did
    Jan 29, 2018 at 16:13

This theorem will be helpful

$\mathbf {Theorem:}$

Let $X$ have density function $f_X$ and let $A=\{x~:~f_X(x)>0 \}$. If $g$ is strictly monotone on $A$, then $Y=g(X)$ has density

$$f_Y(y)=f_X(g^{-1}(y)) \vert\frac{\partial}{\partial y}g^{-1}(y)\vert.$$


One method is to integrate wrt $x$ to find the CDF and then differentiate it back wrt $y$.

Another is to use the "change of variable transformation", which involves one differentiation.

$\begin{align} \\ f_Y(y) & = f_X{\circ}x(y)\; \Bigg|\frac{\mathrm d x(y)}{\mathrm d y}\Bigg|\tag{1: change of variable} \\[1ex] f_X(x) & = 3x^2\tag{2 given} \\[1ex] y & = x^2\tag{3 given} \\[1ex] x(y) & = \pm\surd y\tag{4 $\impliedby 3$} \\[1ex] \frac{\mathrm d x(y)}{\mathrm d y} & = \mp\tfrac 1 2 y^{-1/2}\tag{$5\impliedby 4$} \\[2ex] f_Y(y) & = f_X{\circ}x(y)\; \Bigg|\frac{\mathrm d x(y)}{\mathrm d y}\Bigg|\tag{1} \\[1ex] & = \frac{3y}{|2\surd y|}\tag{$\impliedby 2,4,5$} \\[1ex] & = \tfrac 3 2 \surd y\tag{7} \\[1ex]\sup(f_X) = [0,1] & \implies \sup(f_Y)=[0,1]\tag{8$\impliedby 3$} \end{align}$

This is because: $\displaystyle\frac{\operatorname d}{\operatorname dy}\int_{\sup(f_X)} f_X(x) \operatorname d x = \int_{\sup(f_Y)} f_X{\circ}x(y) \bigg|\frac{\operatorname d x(y)}{\operatorname d y}\bigg|\operatorname d y$

So if we do not need the CDF, this technique might save effort.   It is also handy when the pdf can not be readily integrated (see: Gaussian Normal Distributions).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.